Extracapsular versus intracapsular allograft nephrectomy: impact on allosensitization and surgical outcomes - Touma, Naji J. (Canadian Medical Association, 2011)
INTRODUCTION: Our objective was to compare the impact of extra-capsular (ECAN) versus intracapsular allograft nephrectomy (ICAN) on allosensitization and surgical outcomes. METHODS: Between 1990 and 2004, 96 allograft nephrectomies were performed at our institution. Of these, 29 procedures were performed within 1 month of the transplant and were therefore omitted from analysis. Overall, the results of 44 ECAN and 23 ICAN were reviewed. RESULTS: The mean operative times were 110.9 versus 130.4 min for ICAN versus ECAN (p = 0.02) and the estimated blood loss was 226 mL for ICAN versus 483 mL for ECAN (p = 0.004). Intraoperative and postoperative complications were low using either technique and differences were not statistically significant. Overall, the preoperative to postoperative change in the percentage of panel reactive antibody was +2.1% for ICAN versus +1.2% for ECAN (NS) at 3 to 12 months postoperatively, respectively (NS). The percentage of patients relisted was 33.3% versus 54.3% (NS), and the percentage of patients re-transplanted once relisted was also very similar: 63.2% for ECAN versus 66.7% for ICAN (NS), after a mean follow-up of 4.5 and 8.4 years, respectively. CONCLUSIONS: ICAN can be performed with shorter operative times and less blood loss versus the extracapsular approach. As well, this operative approach does not appear to affect allosensitization and the ability to re-transplant patients.